ARTIFICIAL INTELLIGENCE LEADING THE PEOPLE (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2024)
In modern times, the development of artificial intelligence and its invasion in all areas of public life (including art) has opened a debate that announces, once again, the death of art. The artificial fights against the natural to legitimize its existence through truth and untruth. For some people, creativity is at risk in order to trivialize, for others it is just a matter of pure fakes or copies that violate intellectual property rights. The main objective of this article is to put the ideas in context by answering the following questions: what is and what is not artificial intelligence, what is and what is not plagiarism, and what is and what is not useful in this conflict?
Keywords: artificial intelligence; art; copyright; plagiarism; copy; fakes